The Dialect Choice in the Epigrams on Myron's Cow - Orłowska, Ewa (Polskie Towarzystwo Filologiczne, 2023)
The aim of this paper is to analyse the choice of dialect as a literary device in the series of epigrams on Myron’s Cow. The epigram series in the Greek Anthology consists of 36 epigrams with one preserved in P. Mil. Vogl. VIII 309. The epigrams are composed in Attic-Ionic, Doric, and also mixed dialects. I attempt to explain the probable purpose of using these dialectal forms and the intended poetic effect. Firstly, I analyse and compare probably the oldest epigrams in the series (AB 66 by Posidippus in Attic-Ionic and HE 88 by Leonidas in Doric), which already differ in their dialect usage. There is no easy explanation for the choice of Doric in the epigram by Leonidas. However, an analysis and comparison of the successive imitations of these epigrams may offer some answers. Perhaps the ekphrastic and bucolic nature of these epigrams plays a role here. Secondly, I present and try to explain interesting dialect choices in the five epigrams by Antipater of Sidon on Myron’s Cow. The last part of the article is devoted to the later epigrams in this series, focusing on the choice of Doric forms and their position in the poems.